Submerged Aquatic Vegetation Patch Size Affects Fish Communities in a Turbid-Algal Lake - Looby, Audrey; Reynolds, Laura K.; Adams, Carrie Reinhardt; Martin, Charles W. (Frontiers in Conservation Science, 2021)
Submerged aquatic vegetation (SAV) is declining worldwide, leading to subsequent reductions in the ecological functions associated with SAV in shallow aquatic ecosystems, including providing habitat for fishes. Extensive restoration efforts are required to reverse this trend, but studies focusing on aquatic vegetation have been uncommon in recent years relative to other primary producers. Evaluations of the most beneficial SAV species and characteristics for fishes are especially rare. Because of the potentially complex and inconsistent responses of fish to different management actions, further research is necessary to evaluate the species-specific and community-level effects of SAV to inform restoration decision-making. To examine what SAV characteristics increase fish habitat use in a turbid-algal lake undergoing restoration, we sampled 29 areas around Lake Apopka, Florida (USA) with fyke nets and trotlines. We examined the impact of eight environmental variables on fish abundance, biomass, community structure, and predation potential. For each approximated 0.6 m2 increase in SAV patch size, total fish biomass catch increased 6.5 g hr-1. Fish community composition based on abundance also changed with an increase in SAV patch size. The number of bait items missing from trotlines, a measure of predation potential, was most affected by water temperature, wind speed, and time of day, but not by the SAV variables tested. These results expand existing knowledge of fish habitat use of SAV and will inform future management efforts to conserve and restore fish communities by focusing on specific SAV characteristics such as patch size.